Modeling of inter- and intra-particle coating uniformity in a Wurster fluidized bed by a coupled CFD-DEM-Monte Carlo approach - Jiang, Zhaochen; Rieck, Christian; Bück, Andreas; Tsotsas, Evangelos (Chemical Engineering Science, 2020)
A coupled CFD-DEM and Monte Carlo approach was developed to investigate coating properties in a Wurster fluidized bed by considering gas flow, particle motion, droplet deposition, and the drying and solidifying of droplets on particle surfaces. Based on the spherical centroidal Voronoi tessellation (CVT), the Monte Carlo approach can model the deposition and splashing of spray droplets on the surface of individual particles. The capillary force induced by liquid bridges between particles was accounted in the DEM to investigate its influence on the coating and agglomeration behavior. The new model can provide information about the cycle time distribution, residence time distribution, coating coverage, uniformity of porosity (influenced by splashing) and layer thickness distributions on each individual particle (intra-particle) and in the particle population (inter-particle). The simulation results are compared with experimental data on residence time and intra-particle layer thickness distributions. Good agreement is observed between the simulation and the measurements.
CRIS-Team Scopus Importer:2019-10-29
Keywords: CFD-DEM; Coating; Monte Carlo; Surface coverage; Wurster fluidized bed

PTV experiments and DEM simulations of the coefficient of restitution for irregular particles impacting on horizontal substrates - Jiang, Zhaochen; Du, Jiajie; Rieck, Christian; Bück, Andreas; Tsotsas, Evangelos (Powder Technology, 2020)
For systems of particles with irregular shapes, the collisions between particles and between particles and walls are highly complex and strongly related to the contact geometry. In this work, the collision behavior between irregular maltodextrin particles (with a characteristic size of approximately 100 μm) and horizontal substrates was experimentally measured by an improved particle tracking velocimetry (PTV), which simultaneously reconstructed the trajectories of many particles during the process of free fall and rebound. In addition, the measurement data were compared with DEM simulations using the multi-sphere model and the superquadric model, regarding the distributions of total and normal coefficients of restitution and corresponding relationships with the rotational speed after collision and the absolute difference of incidence angle and rebound angle. Compared to the superquadric model, the multi-sphere model well predicts the macroscopic particle-wall collision behaviors of irregular non-convex particles.
CRIS-Team Scopus Importer:2019-11-29
Keywords: Coefficient of restitution; Irregular non-convex particle; Multi-sphere; Non-spherical DEM; PTV; Superquadric

PTV measurement and DEM simulation of the particle motion in a flighted rotating drum - Zhang, Lanyue; Jiang, Zhaochen; Weigler, Fabian; Herz, Fabian; Mellmann, Jochen; Tsotsas, Evangelos (Powder Technology, 2020)
To investigate the particle motion in the flighted rotating drum (FRD), a laboratory drum with four rectangular flights is horizontally arranged and filled with plastic particles in this work. The FRD is operated by varying the drum rotating speed (10, 20, and 30 rpm) and filling degree (10, 15, and 20%). The particle tracking velocimetry (PTV) method and DEM simulation (with LIGGGHTS software) are applied to analyze the particle movements. The results have shown that, as the drum rotating speed is increased, the holdup ratio and cascading rate of an individual flight increase. The drum rotating speed also affects the particle ratios in three phases and the falling time distribution of the dilute phase. Moreover, the average velocities and granular temperatures of the particle system in FRD increase as the drum rotating speed increases and the filling degree decreases. Good agreements are observed between the PTV measurements and DEM simulations.
CRIS-Team Scopus Importer:2020-01-21
Keywords: DEM; Flighted rotating drum; Granular temperature; Particle motion; Particle velocity; PTV